PEMBEKALAN TENTANG KURIKULUM MERDEKA BELAJAR BAGI GURU DAN TENAGA KEPENDIDIKAN KATOLIK SE-PAROKI WINI DAN WEKFAU DI KEUSKUPAN ATAMBUA - Siri, Theodorus Asa; Sesfao, Marianus; Cornelis Usboko, Wilibrordus (Universitas 17 Agustus 1945 Semarang, 2024)
Paulo Freire’s concept of liberal education is still not implemented in the world of education in developing countries. Educational actors still adhere to the banking system to oppress students. This study raises a social correlation between educators and students called school family kinship. The education curriculum needs to be used as an indicator of success in terms of the intelligence of the children. The curriculum has continued to transform since 1947 to 2022 but has not found its identity. Now, the independent learning curriculum is intensively grounded, but there are gaps between regions and between socio-economic groups in terms of learning quality. The implementation of the independent learning curriculum is considered not to have a significant positive effect in the outermost and marginalized areas. Therefore, the old pattern called banking system of education is still used. Students are considered empty piggy banks that must be filled by the teacher. Teachers are still recognized as the all-knowing in knowledge that must be poured into the brains of students. As a result, students can only follow what is transferred by the teacher. This is the basis for the author to try to provide briefings to Catholic teachers and education personnel in Wini and Wekfau parishes regarding the implementation of an independent curriculum in Catholic Schools. This study uses qualitative methods with observation techniques carried out in coastal parishes (Wini) and in the mountains (Wekfau) in terms of geographical location to find out the similarity of perceptions of the independent curriculum. This study applies a qualitative method with observation techniques carried out in the coastal parish (Wini) and in the mountains (Wekfau) in terms of geographical location to find out the similarities in perceptions of the implementation of the independent curriculum in two different areas.